Teaching “Changes in Electrical Energy to Light” to Students with Intellectual Disabilities in Junior High School - Hermawan, Budi; Hufad, Achmad; Rochyadi, Endang; Maryanti1, Rina; Sunardi, (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to find out how to teach changes in energy (electricity to light energy) in daily life to students with intellectual disabilities. This study uses a single subject research (SSR) approach with pre-test and post-test. The sub-jects of this study were three students at Bandung Extraordinary School. Teaching is delivered using an experimental demonstration method. The experimental demonstration is carried out by observing the changes in the form of electrical energy into light energy in series and parallel electrical energy. The results showed that difficult subjects, such as the change of energy from electrical energy to light energy can be taught to DHI students. As many as 67% can understand the material being taught. The reason for achieving success is because using the experimental demonstration method helps DHI students easily understand the subject matter. DHI students find it difficult to understand a complex and abstract concept. Thus, to understand what the teacher has taught learning must be made as attractive as possible according to the needs of children.